Hypercalcemia and diffuse osteolytic lesions in a 45-year-old patient with myeloid sarcoma with megakaryocytic differentiation. Issue 2 (1st January 2016) - Goud, Aditya; Abdelqader, Abdelhai; Dahagam, Chanukya; Jabaji, Ramez; Kumar, Pallavi; Aboulafia, Albert; Selinger, Stephen
Abstract : Acute megakaryocytic leukemia is a rare form of acute myeloid leukemia that carries a poor prognosis. As most cases of osteolytic lesions are due to plasma cell and myeloid malignancies, maintaining a broad differential directly influences clinical course. We document a 45-year-old patient with progressive constitutional symptoms, osteolytic bone lesions in the setting of hypercalcemia, who developed acutely worsening pancytopenia. The diagnosis of myeloid sarcoma with megakaryocytic differentiation was made after obtaining tissue from osteolytic bone that stained strong for CD34. Immunohistochemical testing underscores the importance of how serologic and urine testing remains limited and can delay early diagnosis in this disease.